Methodology to Evaluate Economic Viability Plans and Digitalization Strategies in Private Social Education Centers - Ricardo Francisco Reier Forradellas; Javier Jorge-Vázquez; Sergio Luis Náñez Alonso; Ricardo Salazar Valdivia (MDPI AG, 2021)
The Spanish educational system is characterized by the coexistence of three different models of production and provision of education: public, subsidized and private. Within the privately-owned centers not under the subsidized system, private schools of a social nature stand out. These schools, whose main source of financing comes from the fees paid by the students' families, must implement financial strategies that guarantee their economic viability and allow them to develop their educational project. In a highly competitive environment, the implementation of sound financial strategies and the development of educational innovation policies are critical to ensure their survival. In this context, this study analyzes a methodological proposal that can contribute to guide this strategic policy based on two fundamental pillars: the financial viability of the center and educational innovation through the application of new technologies and innovative teaching strategies. To this end, the case method has been used as the main methodology, obtaining results that considerably improve student satisfaction and that represent economic improvements of more than €100,000 per year. From these results it has been possible to identify different possible scenarios that can condition the financial viability of the educational center, the dropout rate and the academic performance of the students.